2020
DOI: 10.1001/jamasurg.2020.0046
|View full text |Cite
|
Sign up to set email alerts
|

Service to Others May Be the Answer to Physician Burnout

Abstract: There is a crescendo of attention focused on compassion training in health care. Importantly, this is not just about meeting the needs of patients, but also about learning how compassion can bring personal joy. Some of these concepts can be conceptualized as seva: a service that is performed without any expectation of result or award for performing it. Such services can be performed to benefit other human beings or society. "Seva is an ancient Sanskrit term, which originally referred to the service performed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Fixed duty hours, lack of monetary incentives for working beyond the scheduled duty hours, and insufficient staffing may be other factors responsible. Regular OT team meetings to debrief on cancellations involving all the multidisciplinary stakeholders and time stamping of each of the OT processes may help improve time utilisation [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fixed duty hours, lack of monetary incentives for working beyond the scheduled duty hours, and insufficient staffing may be other factors responsible. Regular OT team meetings to debrief on cancellations involving all the multidisciplinary stakeholders and time stamping of each of the OT processes may help improve time utilisation [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, this strain may lead to compassion fatigue, moral distress, posttraumatic stress, or burnout [ 5 , 6 ]. On the other hand, the increased workload also led to more or new meaning and appreciation of the medical profession and could increase joy, job satisfaction, and work engagement of intensivists, thus, protecting them from burnout [ 7 , 8 ]. The prevalence of burnout among Dutch intensivists was found to be 4.4% in a nationwide online study in 2013 [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The word "Seva" is of Sanskrit origin, which means the performance of duties and serving mankind without the greed for reward or gifts. Similarly, the burnout of surgeons in hernia repair can be taken care of if the repair is done with full dedication and commitment [ 11 ]. In another study conducted by Vora et al, they also concluded that by using a mixed methodology, the deficiency of trust from the patients can be mitigated by good communication between doctor and patient, particularly that all patients should be managed equally irrespective of their paying capacity [ 12 ].…”
Section: Discussionmentioning
confidence: 99%